Elaboración de un plan de mejora del clima laboral para la Unidad Educativa Santa Juana de Chantal, Otavalo, Imbabura - Boada Gualsaquí, Jonathan Ramiro (2023)
The objective of this research is to develop a plan to improve the working environment in the Santa Juana de Chantal Educational Unit located in Otavalo, Imbabura province. This is a descriptive research, with a non-experimental and cross-sectional design. It focuses on the work environment and it is based on quantitative data to obtain accurate results. It seeks to know the perception of the work environment of the Institution's collaborators and, with the data analyzed, an improvement plan will be built. The sample is made up with 24 collaborators from the administrative area and 43 teachers, in total 4 men and 20 women in the first case, and 12 men and 31 women in the second case. The research will include to all the members of the Institution, without any exclusion criteria. For an effective data collection, the Google Forms program was used, the survey was applied taking into account the objectives and the nature of the information to be collected. The interpretation of the data was carried out with the Likert scale measurement method. The results of the survey about work environment in the Educational Unit 'Santa Juana de Chantal' show a positive perception by teachers and administrative staff of several important aspects of the work environment in the institution, taking into account the following dimensions: autonomy, trust , support, recognition, equity and innovation. To verify the results issued through the survey, it was decided to conduct an interview with the Rector of the Institution, which could show some problems, according to job insecurity, low salary, not having a third level degree in education, docile staff and labor instability and thus determine the problems in depth.